Effect of packaging materials on the shelf‐life of vermicelli supplemented with enzyme processed kinnow pulp residue. (9th September 2021) - Singla, Gisha; Panesar, Parmjit S.; Sangwan, Rajender S.; Krishania, Meena
Abstract: Packaging material has important role in the shelf‐life of food products. The present study has been focused on effect of packaging materials‐low density polyethylene (LDPE) pouch and bi‐axially oriented polypropylene (BOPP) pouch on the quality of vermicelli produced by supplementation of debittered kinnow pulp residue with storage time. The moisture content of supplemented vermicelli increased from 5.11 to 7.12% in LDPE pouches after 90 days and 5.11 to 6.98% in BOPP pouches after 180 days. Hardness decreased from 28.89 to 13.42 N in LDPE pouches after 90 days and 28.89 to 15.98 N in BOPP pouches after 180 days ( p  ˃ 0.05) during storage conditions. The total plate count was found to be more in vermicelli stored in LDPE pouches as compared to samples in BOPP pouches. On the basis of overall acceptability, the supplemented vermicelli samples packed in LDPE pouches were stable up to 90 days and in BOPP up to 180 days. BOPP has potential for commercial packaging for antioxidant‐rich extruded food products without adversely affecting their physiochemical and sensory properties. Practical applications: Food industry waste consists of high amount of nutrients and minerals and fiber content, but due to bitterness causing compounds especially in citrus byproducts, these cannot be used directly in preparation of healthy extruded products. Enzyme debittering of kinnow juice industry byproducts was carried out and then supplemented into vermicelli. Study has been focused upon the storage stability of the supplemented extruded product in different packaging materials. The supplementation of enzyme debittered kinnow pulp residue can enhance the antioxidant activity and dietary fiber content of vermicelli besides value addition of the byproduct. Furthermore, BOPP has potential for commercial packaging without adversely affecting their physiochemical and sensory properties as compared to LDPE pouches. Abstract :